PRESTIGIOUS PERCEPTION OF POTATO FARMING: AN OVERVIEW OF THE ECONOMY, SOCIO-CULTURE, AND ITS EXISTENCE - Cahyo Nur Muhammad; Yuli Hariyati (Socio-Economics/Agribusiness Department, 2021)
Potato farming has been developed by the Tengger Tribe in Ngadisari Village, Sukapura District, Probolinggo Regency. These tribal people cultivate various agricultural commodities, but they feel prestige when farming potatoes. This prestigious perception underlines the research that aims: 1. To determine the existence of the prestigious perception, 2. To analyze economically whether potato farming supports the prestigious perception that it can provide higher profits than other plants cultivated on the same land, and 3. Are there socio-cultural reasons for the prestigious perception of potato farming. This study used quantitative methods with 30 respondents selected by purposive sampling. The description method used to know the existence and identify social-cultural factors of the prestigious perception. To prove that economically, analyzed by comparing the potato’s farming income with non-potato on the same land. The result showed: 1) 77 % of respondents still feel prestige if they cultivate potatoes, 2) economically, potato farming had a higher income than non-potato farming, and 3) socio-cultural factors that support Tengger Tribe feel prestige: a. passed down from generation to generation, b. farming complexity challenges, and c. the needs and equality of female workers.